1982
DOI: 10.1002/jctb.5030320730
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration reactions of fructose in non‐aqueous media

Abstract: Procedures for the dehydration of fructose in non-aqueous solvents using Amberlyst 15 strong acid resins and amine salts as catalysts have been developed to give hydroxymethylfurfural (HMF), hydroxymethylfurfural ethers and laevulinate esters with high carbon recoveries. These procedures allow of easy 'scale-up' and recovery of catalyst and solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 7 publications
1
74
2
2
Order By: Relevance
“…To overcome restrictions in conversion and selectivity, dehydration processes have also been conducted in non-aqueous high-boiling organic solvents (e.g., PEG-600 [36] and DMSO [33,37,38]), in sub-and supercritical fluids (acetone/water, methanol and acetic acid [15][16][17]), and in ionic liquids [29,[39][40][41][42]. For example, Musau et al [38] report on the catalystfree synthesis of 5-HMF in DMSO at 150°C, achieving 92 % yield after 2 h. Bicker et al [15] achieved 99 % fructose conversion and 77 % 5-HMF selectivity in a subcritical acetone/water mixture at 180°C and 200 bar.…”
Section: Hmf Synthesis: Status Quomentioning
confidence: 99%
“…To overcome restrictions in conversion and selectivity, dehydration processes have also been conducted in non-aqueous high-boiling organic solvents (e.g., PEG-600 [36] and DMSO [33,37,38]), in sub-and supercritical fluids (acetone/water, methanol and acetic acid [15][16][17]), and in ionic liquids [29,[39][40][41][42]. For example, Musau et al [38] report on the catalystfree synthesis of 5-HMF in DMSO at 150°C, achieving 92 % yield after 2 h. Bicker et al [15] achieved 99 % fructose conversion and 77 % 5-HMF selectivity in a subcritical acetone/water mixture at 180°C and 200 bar.…”
Section: Hmf Synthesis: Status Quomentioning
confidence: 99%
“…Previous work has shown that high yields of HMF from fructose can be obtained in high-boiling solvents such as pure DMSO; however, the HMF product thermally degrades upon purification from DMSO, leading to energy-intensive separation procedures. [68] Importantly, by adding small amounts of aqueous-phase modifiers (such as DMSO and PVP) in the biphasic reactor system, the selectivity can be improved from 60 to 75 %. The effectiveness of the process was further improved by optimizing the partitioning of HMF product into the organic phase, both to minimize degradation of HMF in the aqueous phase and to achieve efficient recovery in the product isolation step.…”
Section: Reviews 7176mentioning
confidence: 99%
“…Nach älteren Arbeiten können in hochsiedenden Lösungsmitteln wie DMSO hohe Ausbeuten an HMF aus Fructose erzielt werden, doch zersetzt sich das HMF bei der destillativen Abtrennung von DMSO, sodass kostenintensive Reinigungsverfahren nötig sind. [68] Bereits durch geringe Zusätze von Modifikatoren (z. B. DMSO oder PVP) zur wässrigen Phase lässt sich die Selektivität auf 60 bis 75 % erhöhen.…”
Section: Reformierung Von Oxygeniertenunclassified